STRATEGI PENGEMBANGAN LINGKUNGAN SEBAGAI KAWASAN DESA WISATA DI SENDANGSARI, PAJANGAN, BANTUL, DIY - Nur Endah Januarti (Jurnal Sosiologi Reflektif, 2017)
The article describes the strategy of environmental development as a tourist village area conducted in Sendangsari. Research background of the emergence of UU Desa and UU Keistimewaan DIY. That underlies various rural areas in developing the environment. In Sendangsari, the environmental management strategy is carried out as a form of tourism development. The data obtained through research conducted by qualitative descriptive method and data collection technique through observation, interview and documentation. The informants involved in the research process are the Village Head, the village management board ie LPMD, PKK, Karang Taruna and the Tourism Actors, the Head of the Sadar Wisata Group. It also involves the Office of Culture and Tourism of Bantul Regency as a government stakeholder. The result of the research shows that the strategy implemented by Sendangsari Village in the effort of environmental management as the implementation of UU Desa and UU Keistimewaan DIY are 1) Environmental mapping in the form of village potency; 2) Social empowerment to optimize tourism potential; 3) Utilization of environment as Tourism Village development area; 4) The carrying capacity of the government in the management of the Tourism Village.Artikel ini menjelaskan tentang strategi pengembangan lingkungan sebagai kawasan desa wisata yang dilakukan di Sendangsari. Penelitian dilatarbelakangi munculnya UU Desa dan UU Keistimewaan DIY sehingga mendasari berbagaikawasan perdesaan dalam mengembangkan lingkungan. Di Desa Sendangsari strategi pengelolaan lingkungan dilakukan sebagai bentuk pengembangan pariwisata. Data-data diperoleh melalui penelitian yang dilaksanakan dengan metode kualitatif deskriptif serta teknik pengumpulan data melalui observasi, wawancara dan dokumentasi. Informan yang terlibat dalam proses penelitian adalah Kepala Desa, pengurus lembaga desa yakni LPMD, PKK, Karang Taruna dan Pelaku Pariwisata yakni Ketua Kelompok Sadar Wisata. Selain itu juga melibatkan Dinas Kebudayaan dan Pariwisata Kabupaten Bantul sebagai stakeholder pemerintah. Hasil penelitian menunjukkan strategi yang dilaksanakan Desa Sendangsari dalam upaya pengelolaan lingkungan sebagai implementasi UU Desa dan UU Keistimewaan DIY adalah 1) Pemetaan lingkungan berupa potensi desa; 2) Pemberdayaan sosial untuk optimalisasi potensi wisata; 3) Pemanfaatan lingkungan sebagai kawasan pengembangan Desa Wisata; 4) Daya dukung pemerintah dalam pengelolaan Desa Wisata.Keywords: Environment, Sendangsari, Tourism Village